A Comprehensive Review: Advances in Mesenchymal Stem Cell Applications for Burn Wound Repair - Hui-Juan Zhang; Jing-Jie Ming; Hong-Xiao Zhang; Shao-YI-Han Fang; Quan-Wen Liu; Hong-Yan Zhang (Stem Cells International)
Tissue repair following skin injury is a complex process that encompasses hemostasis, inflammation, tissue cell proliferation, and structural remodeling. Mesenchymal stem cells (MSCs) are derived from the mesodermal layer of tissues and possess multidirectional differentiation potential and self-renewal capabilities. MSCs from various sources, including the bone marrow, adipose tissue, dental pulp, umbilical cord, and amniotic membrane, have demonstrated effectiveness in promoting skin injury repair. They aid in this process by fostering the formation of new blood vessels in damaged tissues, self-renewal, or transdifferentiation into skin or sweat gland cells. Moreover, MSCs promote the proliferation and migration of skin cells, reduce wound inflammation, and restore the extracellular matrix through paracrine secretion. In this paper, we review recent findings regarding MSCs and their role in burn wound repair. Additionally, we explore the potential of combining MSCs with various biomaterials for treating burn wounds and analyze clinical cases wherein MSCs were administered to patients, offering insights into ongoing research on MSC-based therapies for skin injuries.